Assessment of biosafety and biorisk management practices among medical laboratory students in two institutions in Uganda - John Roberts Padde; Winnie Akiteng; William Edema; Saad Mahjub Atiku; Julius Tibyangye; Job Tekakwo; Cosmas Andruga; Derick Hope; Benson Musinguzi; Jean Brenda Gesa; Lawrence Amadile; Robert Agondua (Elsevier, 2022)
Medical laboratory workers handle clinical specimens, which are a threat of exposure to infectious agents. Notably, medical laboratory science students report for internships with only theoretical knowledge of biosafety and biorisk management practices, predisposing them to a higher risk of laboratory hazards. In this study, we assessed the influence of entry-level students' adherence to practices and attitudes towards biosafety and biorisk management during the Internship. An online survey tool was used to explore the practices and attitudes towards laboratory biosafety and risk management. Of the 96 students, 60 (62.5%) anonymous responses were received, and of these, 60.3% were direct entrants, and 32.8% were diploma entrants. Most (91.7%) of the students attended hospital internships, with 60.2% in Biosafety Level (BSL)-2 laboratories and 70.2% rotating in all the core areas of laboratory medicine. The 8.3% who did not attend any internship were under the direct entry category. Exposure to biohazards was not significantly associated with laboratory safety level and student entry category (P> 0.05). Recommended laboratory biosafety practices were not significantly associated with the safety level of the laboratory and student entry category (P> 0.05). Poor attitudes towards certain laboratory biosafety practices were not significantly associated with the biosafety level of the training laboratory (P> 0.05), whereas training (P = 0.021) and clean-up procedures (P = 0.048) were associated with laboratory safety levels, respectively. The direct entrants had no access to BSL-3 laboratories, and this category of students had a negative attitude towards internship attendance. Therefore, there is a need to create a multi-channel full range laboratory biosafety and biorisk management teaching reforms based on practical application, real case studies, and laboratory simulation to be incorporated into the curriculum to benefit the direct entrant.